2016
DOI: 10.1002/2015jc011480
|View full text |Cite
|
Sign up to set email alerts
|

The complementary role of SMOS sea surface salinity observations for estimating global ocean salinity state

Abstract: Salinity is a key ocean state property, changes in which reveal the variation of the water cycle and the ocean thermohaline circulation. However, prior to this century, in situ salinity observations were extremely sparse, which decreased the reliability of simulations of ocean general circulation by ocean and climate models. In 2009, sea surface salinity (SSS) observations covered the global ocean via the European Space Agency's Soil Moisture and Ocean Salinity (SMOS) mission, and several versions of global SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 61 publications
2
20
2
Order By: Relevance
“…Progress have been recently made in SSS observation, thanks to the new satellite SSS measurements provided by the European Space Agency Soil Moisture and Ocean Salinity (SMOS mission led by ESA in collaboration with CNES and CDTI) [Reul et al, 2012] and by the Aquarius/SACD mission [Lagerlof, 2012] that are available from 2010 to present and 2011 to 2015, respectively. Satellite measurements offer the opportunity to observe the SSS with an unprecedented resolution about 50-150 km, 3-7 days [Lee et al, 2012[Lee et al, , 2014Hernandez et al, 2014;Reul et al, 2014aReul et al, ,2014bLu et al, 2016]. In the tropical Atlantic, satellite observations allow to monitor the seasonal SSS variability [Tzortzi et al, 2013] and to detect tropical instability waves (TIWs) [Lee et al, 2014].…”
mentioning
confidence: 99%
“…Progress have been recently made in SSS observation, thanks to the new satellite SSS measurements provided by the European Space Agency Soil Moisture and Ocean Salinity (SMOS mission led by ESA in collaboration with CNES and CDTI) [Reul et al, 2012] and by the Aquarius/SACD mission [Lagerlof, 2012] that are available from 2010 to present and 2011 to 2015, respectively. Satellite measurements offer the opportunity to observe the SSS with an unprecedented resolution about 50-150 km, 3-7 days [Lee et al, 2012[Lee et al, , 2014Hernandez et al, 2014;Reul et al, 2014aReul et al, ,2014bLu et al, 2016]. In the tropical Atlantic, satellite observations allow to monitor the seasonal SSS variability [Tzortzi et al, 2013] and to detect tropical instability waves (TIWs) [Lee et al, 2014].…”
mentioning
confidence: 99%
“…Previous studies assimilating SMOS [18,21] have used an observation error of between 0.1-0.4 PSU. However, these studies did not focus on river plumes.…”
Section: Assimilation Schemementioning
confidence: 99%
“…While the more traditional Argo floats provide relatively accurate in-situ salinity profiles, their lack of spatial coverage (typically 3 • by 3 • ) is a significant limitation. In 2009 the European Space Agency (ESA) launched the first satellite to monitor surface sea salinity under the Soil-Moisture-Ocean Salinity (SMOS) mission [18] providing global coverage of surface salinity. Köhl et al [19] assimilated SMOS but found no benefits to the global model salinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the possibility of accurately re-assessing historical HSLA; (2) nowadays, we still have more observations in the upper layer, since sea surface salinity can be observed from satellites (such as the Soil Moisture Ocean Salinity (SMOS) mission by the European Space Agency and the NASA Aquarius mission). Assimilating the upper ocean surface salinity into ocean models will have the potential to significantly improve the model simulation [46,47].…”
Section: The Role Of Salinity In Regional Sslamentioning
confidence: 99%